Energy Consumption, CO2 Emissions and Economic Growth: A Causality Analysis for Malaysian Industrial Sector - Tan, Chiang-Ching; Tan, Syvester (International Journal of Energy Economics and Policy, 2018)
Malaysia is currently a developing country which is from agriculture based to manufacturing and service-based economy by implementing Industrialisation Plan in 1985. Thus, the country is consuming more energy due to the rapid industralisation hoping to fully transform into a fully industralised country in future. It is decisive for the government to develop policies to minimize energy consumption and reducing CO2 emissions to protect the environment without impairing the economy. The study looks into the causal relationship between real income (Y), energy consumption (EC) and carbon dioxide (CO2) emission in Malaysian industrial sector during the period of 1980-2014, by applying the time-series econometric techniques. Major findings of this paper consists of long-run relationship exists between Y, EC and CO2 emissions; unidirectional causality relationship from EC and CO2 emissions to Y in both short and long-run; and results of the variance decompositions suggest that the impact of Y and EC towards CO2emissions becomes noticeable only over the longer period of time. Keywords: Industrial Sector, Energy Consumption, Carbon Dioxide Emission JEL Classifications: L16, Q43, O13